2023
DOI: 10.4103/2221-1691.369610
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, antimicrobial, and α-glucosidase inhibitory activities of saponin extracts from walnut (Juglans regia L.) leaves

Abstract: Objective: To investigate the relationship between triterpenoid saponin content and antioxidant, antimicrobial, and α-glucosidase inhibitory activities of 70% ethanolic, butanolic, aqueous, supernate and precipitate extracts of Juglans regia leaves. Methods: Triterpenoid saponins of different Juglans regia leaf extracts were measured by the vanillin method. Antioxidant activity was evaluated against DPPH and ABTS free radicals. We also assessed α-glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…This method has been frequently considered to evaluate the antioxidant activities of food materials (Koocheki et al, 2022). Some researchers have reported the antioxidant activity of walnut leaves (Fernández-Agulló et al, 2019;Pereira et al, 2008). In our research, all fractions showed relatively high antioxidant activity.…”
Section: Estimation Of the Antioxidant Activity By Dpph Methodssupporting
confidence: 49%
See 2 more Smart Citations
“…This method has been frequently considered to evaluate the antioxidant activities of food materials (Koocheki et al, 2022). Some researchers have reported the antioxidant activity of walnut leaves (Fernández-Agulló et al, 2019;Pereira et al, 2008). In our research, all fractions showed relatively high antioxidant activity.…”
Section: Estimation Of the Antioxidant Activity By Dpph Methodssupporting
confidence: 49%
“…The inhibition zone diameters were measured using a ruler with 0.5 mm accuracy, and the average radius of the inhibition zone in mm was calculated from three measurements on three different plates. Control plates inoculated with each sensitive indicator microorganism were also prepared (Fernández-Agulló et al, 2013).…”
Section: Antimicrobial Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that compounds extracted from plants, animals, and microorganisms have antibacterial activity and are expected to be novel antibacterial agents. Extensive experiments have demonstrated the antibacterial effects of walnut extract [ 69 , 70 , 71 , 72 , 73 ]. In fact, EeDJF has promising antibacterial activity.…”
Section: Extractsmentioning
confidence: 99%
“…The walnut (Juglans regia L.) is among the medicinal plants of interest [31][32][33] due to its rich content of antioxidants such as flavonoids, phenolic acids (notably ellagic acid), melatonin, folate, gamma-tocopherol (vitamin E), selenium, juglone, and proanthocyanidins [34][35][36][37] in various organs (kernels, shells, roots, and leaves). Several studies have shown that J. regia, along with its extracts and essential oils, exhibits a range of biological and pharmacological properties, including antibacterial, antifungal, antioxidant, and anti-inflammatory activities, demonstrating effectiveness against a broad spectrum of pathogens [38][39][40][41][42]. Innovative modern biotechnologies are increasingly focused on developing medicinal crops that are rich in biologically active compounds via manipulating growth conditions to enhance the production of these valuable compounds.…”
Section: Introductionmentioning
confidence: 99%